KONTRIBUSI METODE PEMBELAJARAN, MOTIVASI BELAJAR DAN LATAR BELAKANG JURUSAN DI SEKOLAH MENENGAH TERHADAP PRESTASI BELAJAR MAHASISWA AKPER PANTI KOSALA SURAKARTA - Endang Dwi Ningsih; Rizky Fajar Septiana (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Background: a Learning achievement is inseparable from a learning activities because alearning process must provide a learning outcomes. By a high learning achievementindicates that the students have a good understanding of the knowledge. The learningachievement of a person is determined by internal and external factors that concerningthree fundamental aspects of the learning process are namely the input, the process andthe output. On the input aspects the determinant are the individual background, thefacilitator, the method, the learning motivation and environment in which influencing thelearning process so as to give output In the form of the learning achievement. Related tothe above, the researcher is interested to do a research that concerning about thecontribution of the learning method, the learning motivation and the majors studyBackground at the high School to the learning achievement of AKPER Panti KosalaSurakarta students. Research objectives: to know the contribution of the learningmethod, the learning motivation and the background of the majors study at the highschool to the student learning achievement of AKPER Panti Kosala Surakarta students.Research subject: research sample of 162 students of AKPER Panti Kosala Surakarta.Sampling by simple random sampling.Results : by multivariate test with the double logistic regression test, show the valueNegelkerke R Square 18,7%.Conclusion : That the variable of the learning method, the learning motivation and thebackground of majors study at the high school are jointly affect the learning achievementequal to 18,7% and the rest of which is 81,3% affected by other variable out of theresearch.Keywords: The Learning Method, The Learning Motivation, The Background of themajors study at the high school and The Learning Achievement